PENGARUH DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI KANTOR BUPATI GOWA - Raehan Raehan; Muhammad Najib Kasim; Syarifuddin Sulaeman (Universitas Teuku Umar, 2026)
This study aims to determine the effect of work discipline and compensation on employee performance at the Gowa Regent's Office. The underlying phenomenon of this research is the persistence of employees who exhibit low levels of discipline, such as late arrivals and non-compliance with work procedures, as well as dissatisfaction with the compensation system, which is perceived as not commensurate with the workload. The research method used was quantitative with multiple linear regression analysis. The population in this study was 787 employees, and based on calculations using the Slovin formula with a 10% error rate, a sample of 89 respondents was obtained. Data were collected through a questionnaire consisting of variables of work discipline, compensation, and employee performance. The results showed that work discipline had a positive and significant effect on employee performance, meaning that the higher the level of discipline, the better the performance displayed. Compensation also has a positive and significant impact on employee performance, where a fair and appropriate compensation system can increase employee motivation. Keywords : Work Discipline, Compensation, Employee Performance